Back Cover: Advanced Engineering Materials 1∕2015. Issue 1 (January 2015) - Unknown
<x xml:space="preserve">Abstract</x> A fast, simple and controllable method has been used to prepare GNSs/Al2O3 powders. The cover graphic shows the scheme of the process, which can realize the large‐scale preparation and homogeneous dispersion of GNSs by one‐step. Further details can be found in the article by Jian‐Lin Li, Lian‐Jun Wang and co‐worker on page 29. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>